Development of a mosfet-based radio frequency amplifier for improved signal reception (2010)
It is highly desireable that the information routed from a source reaches the audience or destination with little or no interference or distortion. In radio wave propagation, at times, the signal received at the destination arrives with some form of noise; which makes the message unintelligible enough for the listener. And at some other times, the signal cannot even be picked up at the recieving end. Hence, a device that will obtain the maximum possible noise is desirable. In this research work, we designed a preamplifier using a Metal Oxide Semiconductor Feild Effect Transistor (MOSFET) to filter noise and to produce clearer pictures and better sound quality with increased directivity or gain. The MOSFET-based preamplifier was analyzed in performance and compared with the usaul Bipolar Junction Transistor (BJT) type. The result in analytical form showed a gain of 25.1dB in the MOSEFT-type and a 7.93dB in BJT. The designs were simulated with a simulator package, Electronic workbench 5.0. The result obtained agrees with the analytical results. However, for better monitoring of antenna behavior, particularly over a band of frequencies, a network analyzer is suggested. And for a more accurate and stable preamplifier circuit, a microprocessor can be considered for future design.